Early epidermoid carcinoma. A case presentation - Lidia Torres Ajá; Julian Viera Llanes (Medisur)
The early epidermoid carcinoma is considered the strangest breast tumor with an incidence that only represents from 0,04 to 0,075 % out of all malignant tumors of the breast. It is a variety of the metaplastic carcinoma constituted by pavement keratinizing cells with an inconstant presence of fusocellular sarcomatoid elements, that reach great volume and frequently present as cystic tumours that may be confused with a breast abscess. This is the case of a 41 year-old white female from Cienfuegos municipality, Cuba, who presented to the provincial Mastology consultation because of a two month follow up of a 5 cm tumor in the right outer upper quadrant of her breast. Surgical removal of the tumor was performed and the result of the biopsy revealed a little differentiated epidermoid carcinoma. At present the patient has no metastasis and receives treatment at the outpatient. Its unusual presentation has led this case to be published.